THE INTEGRATION OF SPIRITUAL BASED HOLISTIC EDUCATION AND HOLISTIC HEALTH TOWARDS HOLISTIC HEALTH EDUCATION (HHE): ISLAMIC PSYCHOLOGY PERSPECTIVE - Achmad Ushuluddin; Siswanto Masruri; Gumilar Rusliwa Somantri; Abd. Madjid (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This paper attempts to pioneer efforts to conceptualize Holistic Health Education (HHE), especially from the perspective of Islamic Psychology. The problem raised in this paper is: how is the conceptualization of Holistic Health Education (HHE) from the perspective of Islamic psychology? What is the determination of spiritual role in Holistic Health Education (HHE)?  What is the new model of relationship between doctors and patients in Holistic Health Education (HHE)? To answer these problems, the author uses the theory of spiritual roles in the perspective of Islamic psychology, holistic health theory, and system philosophy (intersubjective relations). As a result, there are 3 basic principles in Holistic Health Education (HHE), namely spiritualist-educational laboratories that are parallel with God's natural-community relations. In Holistic Health Education (HHE), spirituality and taste or pleasure or substance have a very determinant role, because it is he who perfects human events in his body, who can feel healthy and sick. With the existence of spirit and feeling in the subject, that's what distinguishes it from the object. It is this interior dimension that determines the new model of ethical relations between doctors and patients in Holistic Health Education (HHE), which is referred to as the intellectually intersubjective relationship. Keywords: Holistic education, holistic health, spiritual, psychological, spiritual, human